Mutual Gains? Is There a Role for Employee Engagement in the Modern Workplace? - Alex Bryson (Institute of Labor Economics (IZA), 2017)
I examine the history of employee engagement and how it has been characterised by thinkers in sociology, psychology, management and economics. I suggest that, while employers may choose to invest in employee engagement, there are alternative management strategies that may be profit-maximising. I identify four elements of employee engagement – job 'flow', autonomous working, involvement in decision-making at workplace or firm level, and financial participation – and present empirical evidence on their incidence and employee perceptions of engagement, drawing primarily from evidence in Britain. I consider the evidence regarding the existence of mutual gains and present new evidence on the issue. I find a non-linear relationship between human resource management (HRM) intensity and various employee job attitudes. I also find the intensity of HRM use and employee engagement are independently associated with improvements in workplace performance. I consider the implications of the findings for policy and employment practice in the future.
Keywords: J24; J28; L22; L23; M12; M54; 330; employee engagement; productivity; performance; human resource management; worker wellbeing